Respuesta :

Answer:

Isolate the variable by dividing each side by factors that don't contain the variable.

x = 1

First: distribute 3(x+1)= -2(x-1)+6

3x+3=2(x-1)+6

Then you have too distribute again

3x+3=2(x-1)+6

3x+3= -2x+2+6

Third: add the numbers

3x+3= -2x+2+6

3x+3= -2x+8

Fourth: add the same term to both sides of the equation

3x+3= -2x+8

3x+3-3= -2x+8-3

Fifth: Simplify 3x= -2x+5

Sixth: add same term to both sides of the equation

3x= -2x+5

3x+2x= -2x+5+2x

Seventh: simplify again

5x =5

Eigth: divide both sides of the equation by the same term

5x=5

5x/5 =5/5

Last: Simplify

X=1

ACCESS MORE